Targeted Learning with Speaking Worksheets: Advancing Professional Communication Skills in EFL Higher Education - Hastini, Hastini; Mertosono, Sudarkam R.; Wahyudin, Wahyudin; Eisenring, Moh. Abraham Akbar; Sadilia, Sukmawati (Utamax : Journal of Ultimate Research and Trends in Education, 2025)
As English becomes the lingua franca of professional communication, many higher education institutions still overlook the importance of equipping EFL learners with targeted speaking skills for real-world occupational settings. This study responds to that pressing educational need by exploring the effectiveness of structured speaking worksheets in enhancing students' speaking proficiency and overall engagement in a professional communication course. Conducted through a quasi-experimental pretest-posttest design, the research involved 60 undergraduate English Education students at Tadulako University who were divided into an experimental group using speaking worksheets and a control group receiving conventional instruction. Students' speaking performance was evaluated across five critical dimensions: grammar, pronunciation, fluency, vocabulary, and contextual appropriateness. Engagement levels were measured using structured questionnaires. The results revealed a clear improvement in the speaking abilities of students who used the worksheets, accompanied by stronger motivation, enhanced self-confidence, and increased critical thinking. These gains, when compared to the outcomes of the control group, indicate the pedagogical value of incorporating structured, context-driven speaking materials into classroom instruction. Rather than functioning as simple practice tools, speaking worksheets emerged as dynamic resources that promoted learner agency, active participation, and deeper communicative competence. This study advances English for Professional Purposes by providing empirical support for using responsive, scenario-based materials in EFL instruction. It highlights the value of task-based, learner-centered approaches that connect academic learning with future workplace communication.